The New Keynesian Phillips Curve and the role of expectations : evidence from the Ifo world economic survey - Steffen Henzel; Timo Wollmershäuser (Center for Economic Studies and ifo Institute (CESifo), 2006)
We provide evidence on the fit of the hybrid New Keynesian Phillips curve for selected euro zone countries, the US and the UK. Instead of imposing rational expectations and estimating the Phillips curve by the Generalized Method of Moments, we follow Roberts (1997) and Adam and Padula (2003) and use direct measures of inflation expectations. The data source is the Ifo World Economic Survey, which quarterly polls economic experts about their expected future development of inflation. Our main findings are as follows: (i) In comparison with the rational expectations approach, backward-looking behaviour turns out to more relevant for most countries in our sample. (ii) The use of survey data for inflation expectations yields a positive slope of the Phillips curve when the output gap is used as a measure for marginal cost.
Keywords: E31; C52; 330; inflation expectations; survey data; euro zone; Phillips curve; Phillips-Kurve; Inflationserwartung; Rationale Erwartung; Europäische Wirtschafts- und Währungsunion; Schätzung; EU-Staaten; USA; Großbritannien